Method for separating spectrally overlapping multiphoton upconverted emission bands through spectral power dependence analysis - Galindo, Jefferson A.O.; Pessoa, Allison R.; Serge-Correales, York E. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; de S. Menezes, Leonardo; Amaral, Anderson M. (Elsevier, 2023)
The high quantum efficiency and long lifetimes of upconverting rare-earth-doped systems make luminescence band spectral overlap a particularly common phenomenon, frequently associated with various excitation and relaxation pathways. While it is often considered challenging to experimentally distinguish such overlapping luminescent bands, herein it is proposed a new method based on the different spectral responses of those luminescent lines to the excitation power at a single pumping wavelength laser. A model for the population of the overlapping bands in terms of the pump laser power is considered and fitted for each measured wavelength, resulting in separated spectra for each pathway. The results obtained with the proposed method are considered with direct excitation measurements, showing the effectiveness and simplicity of the method in comparison with more traditional approaches.
Keywords: Lanthanide ions; Multiphoton processes; Spectral overlap; Upconversion